Do’s and Don’ts” for intraarterial chemotherapy for retinoblastoma- What ophthalmologist and interventional radiologist need to know? - Pallav Bhatter; Rajsrinivas Parthasarathy; Vipul Gupta; Srinivas Rao Dusa; Ujjwal Aggarwal; Sima Das; Pallav Kumar (Indian Journal of Ophthalmology)
Intra-arterial chemotherapy (IAC) has emerged as the primary treatment option for retinoblastoma management. It enables the localized delivery of a higher concentration of chemotherapeutic agents (melphalan, carboplatin and topotecan) in the ophthalmic artery, enhancing tumour control and potentially avoiding the need for enucleation. Nevertheless, procedure-related complications have raised concerns. In this article, we outline the various technical considerations for performing safe IAC and minimizing procedure-related complications.